2020
DOI: 10.3390/diagnostics10050272
|View full text |Cite
|
Sign up to set email alerts
|

Paper-Based Detection Device for Alzheimer’s Disease—Detecting β-amyloid Peptides (1–42) in Human Plasma

Abstract: The diagnosis of Alzheimer’s disease (AD) is frequently missed or delayed in clinical practice. To remedy this situation, we developed a screening, paper-based (P-ELISA) platform to detect β-amyloid peptide 1–42 (Aβ42) and provide rapid results using a small volume, easily accessible plasma sample instead of cerebrospinal fluid. The protocol outlined herein only requires 3 μL of sample per well and a short operating time (i.e., only 90 min). The detection limit of Aβ42 is 63.04 pg/mL in a buffer system. This P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…36,52,57,58 Tremendous studies have reported the ELISA application in detecting Ab levels in CSF, human plasma, and serum samples. [59][60][61][62][63][64] Numerous lab-based ELISA kits have now been available in the market with the detection range of 10 to 1000 pg mL À1 and procient of discriminating AD patients with healthy control with good sensitivity (80%) and moderate specicity (83.3%). 52,65 In spite of time-consuming and laborious issues of traditional ELISA, the alternative ELISA kits have been widely developed for amyloid detection, which include paper-based ELISA 63 and digital ELISA.…”
Section: Biomarkers As Crucial Target For Biosensor Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…36,52,57,58 Tremendous studies have reported the ELISA application in detecting Ab levels in CSF, human plasma, and serum samples. [59][60][61][62][63][64] Numerous lab-based ELISA kits have now been available in the market with the detection range of 10 to 1000 pg mL À1 and procient of discriminating AD patients with healthy control with good sensitivity (80%) and moderate specicity (83.3%). 52,65 In spite of time-consuming and laborious issues of traditional ELISA, the alternative ELISA kits have been widely developed for amyloid detection, which include paper-based ELISA 63 and digital ELISA.…”
Section: Biomarkers As Crucial Target For Biosensor Systemmentioning
confidence: 99%
“…[59][60][61][62][63][64] Numerous lab-based ELISA kits have now been available in the market with the detection range of 10 to 1000 pg mL À1 and procient of discriminating AD patients with healthy control with good sensitivity (80%) and moderate specicity (83.3%). 52,65 In spite of time-consuming and laborious issues of traditional ELISA, the alternative ELISA kits have been widely developed for amyloid detection, which include paper-based ELISA 63 and digital ELISA. 66,67 Both of them are cost-effective, easy to operate, and portable and thus suitable for POC diagnostic approach.…”
Section: Biomarkers As Crucial Target For Biosensor Systemmentioning
confidence: 99%
“…23 Similarly, Hsuan Sung et al developed a paper-based enzyme-linked immunoassay sensor (P-ELISA). 24 Although these techniques offered high sensitivity, they still lacked the essential properties suitable for POC devices regrading AD screening. They required complicated procedures, a low-throughput screening assay, and large reagent consumption; for instance, immunoassays based on SPR and P-ELISA require on average 5 h and 90 min standard operating times.…”
Section: Introductionmentioning
confidence: 99%
“…The previous approaches to overcoming the sensitivity barrier was amplifying the signal to a detectable level. For example, digital ELISA confines fluorescent molecules, generated by enzymes, into reaction chambers of less than 50 fL (femtoliter) 4 6 , 8 , 10 , 11 , and plasmonic ELISA generates colorimetric signals with distinct tonality, as plasmonic nanoparticles are aggregated 12 16 . The bio-barcode technique also enhances sensitivity via DNA-aided signal amplification 17 21 and ECAS-CIA (enzyme-cascade-amplification strategy-colorimetric immunoassay) allows the detection of low-abundance proteins by coupling with enzyme cascade amplification 22 .…”
Section: Introductionmentioning
confidence: 99%